2020
DOI: 10.1681/asn.2020040523
|View full text |Cite
|
Sign up to set email alerts
|

Only Hyperuricemia with Crystalluria, but not Asymptomatic Hyperuricemia, Drives Progression of Chronic Kidney Disease

Abstract: BackgroundThe roles of asymptomatic hyperuricemia or uric acid (UA) crystals in CKD progression are unknown. Hypotheses to explain links between UA deposition and progression of CKD include that (1) asymptomatic hyperuricemia does not promote CKD progression unless UA crystallizes in the kidney; (2) UA crystal granulomas may form due to pre-existing CKD; and (3) proinflammatory granuloma-related M1-like macrophages may drive UA crystal-induced CKD progression.MethodsMALDI-FTICR mass spectrometry, immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 98 publications
4
74
0
Order By: Relevance
“…This is consistent with reports indicating that CaOx supersaturation occurs independent of urine pH (3), while in other types of kidney stone disease, an acidic urine pH seems to be necessary for the formation of e.g. uric acid crystals, which in turn causes chronic uric acid crystal nephropathy (9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with reports indicating that CaOx supersaturation occurs independent of urine pH (3), while in other types of kidney stone disease, an acidic urine pH seems to be necessary for the formation of e.g. uric acid crystals, which in turn causes chronic uric acid crystal nephropathy (9).…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiological studies reveal that genetic factors play a pivotal role in kidney stone formation ( 7 , 8 ). To study the pathogenesis of different types of kidney stones or crystal-induced chronic kidney disease ( 9 , 10 ), mice are most commonly used as experimental models. Although studies using genetically modified mouse strains indicate an association of certain genes with CaOx crystal formation ( 11 13 ), the role of the genetic predisposition remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…The same is the case for the inflammation modulating effects in CKD and gout of obesity, type 2 diabetes mellitus and reninangiotensin system activation in the pathophysiology of hypertension, and for the use of statins (which modu late trained immunity in monocytes and macrophages) Management of gout in chronic kidney disease: a G-CAN Consensus Statement on the research priorities and metformin and ω3 fatty acids (which inhibit MSU crystal induced inflammation) [11][12][13] . Additionally, ultra sonography studies have demonstrated renal medullary echogenicity in patients with severe gout 14 , potentially attributable to MSU crystalluria and the development of tophi within the renal medulla 15 . MSU crystal driven inflammation might thus directly affect renal structure and function in patients with gout.…”
mentioning
confidence: 99%
“…Therefore, impaired renal function may lead to an increase in sUA, which may be a decrease in glomerular filtration or a decrease in renal tubular resecretion [17], accompanied by an increase in CRE. Adversely, It has been proved that the level of sUA is closely related to the progression of nephropathy [18,19], which may be related to sUA causing kidney damage by stimulating the adrenaline-angiotensin system and promoting the proliferation of vascular smooth muscle cells [20,21], as well as high uric acid. Symptoms of hyperemia can affect renal hemodynamics and cause glomerular perfusion disorders [22].…”
Section: Discussionmentioning
confidence: 99%